2019
DOI: 10.2106/jbjs.19.01095
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Orthopaedic Residents Identifies Deficiencies in the Understanding of Medical Statistics

Abstract: Background: Biomedical research is essential for optimizing patient care. Research has suggested inadequacies in nonorthopaedic trainees' understanding of study design and biostatistics. This study assesses orthopaedic residents' knowledge of common biostatistical and study design concepts, as well as their confidence in utilizing the medical literature. Methods: A validated survey assessing knowledge and the application of study design concepts was administered to residents at 10 U.S. institutions. The survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Our data demonstrate the lack of reported assumptions in the published orthopaedic literature, which is consistent with the lack of understanding of medical statistics amongst orthopaedic residents [ 20 ]. It remains possible that the underlying assumptions were investigated, but not reported.…”
Section: Discussionsupporting
confidence: 88%
“…Our data demonstrate the lack of reported assumptions in the published orthopaedic literature, which is consistent with the lack of understanding of medical statistics amongst orthopaedic residents [ 20 ]. It remains possible that the underlying assumptions were investigated, but not reported.…”
Section: Discussionsupporting
confidence: 88%
“…19 Statistical content was determined based on the low literacy regarding these concepts seen in prior studies of residents and educators. [8][9][10][11][12][13] A video of the PowerPoint presentation contained in this seminar is available in Appendix A. All figures in the presentation were created by the author using Stata statistical software version 14.2 (StataCorp) from fabricated data for illustrative purposes only.…”
Section: Methodsmentioning
confidence: 99%
“…3 A recent Association of American Medical Colleges survey showed that a majority of medical schools lack specific biostatistics training. 7 This lack of training can contribute to low statistical knowledge among resident trainees [8][9][10][11] and subsequently to low statistical literacy among faculty. [11][12][13] A recent scoping review of clinician-educator faculty development programs found that few programs focus on research or scholarship skills.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge specifically regarding the p-value has been studied in isolation, showing a low amount of positive response [22][23][24]. Nevertheless, in the study of Araoye et al [25], 69% made an adequate interpretation of said value. On the other hand, advanced methods, such as survival analyses including Cox proportional hazards regression and Kaplan-Meier analyses, require more advanced knowledge, which would explain the reason why it also had a percentage of correct answers [26].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%